Analysis of ICT, Power Supply and Human Capital Development in Nigeria as an Emerging Market Economy - Orji, Anthony; Ogbuabor, Jonathan E.; Orji , Onyinye I. Anthony; Okoro, Chinonso; Osondu, Daniel (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
This paper analyzed the impact of information and communication technology (ICT) and power supply on human capital development in Nigeria as an emerging market economy. The study adopted the Classical Linear Regression Model for the empirical analysis. The result showed that ICT, power supply (proxied by electricity consumption) and population impact positively on human capital development, while infant mortality has a negative impact on human capital development in Nigeria. The impact of ICT on school enrolment suggests that technology is fast evolving and new technologies are preferred to old ones. The study, therefore, recommended that Nigeria should follow in the trend of ICT globally in harnessing her human capital endowments. In conclusion, the Nigerian government should harness her ICT and electric power potentials and develop the human capital available to her to prevent the emigration of her human resource endowment to more resilient and promising economies.